A Meta-analysis of the effects of differentiated instruction on English language proficiency - Weganofa, Riza; Mujiono (Universitas Muhammadiyah Sidoarjo, 2025)
This meta-analysis systematically examined the effects of differentiated instruction (DI) on English language proficiency, addressing the growing need for instructional approaches that address diverse student profiles․ Seven empirical studies published between 2017 and 2024 were included. The overall pooled mean difference was 2․92 with a 95% confidence interval [1․64–4․19], indicating significant improvements in learners' grammar, reading comprehension, and fluency․ A high heterogeneity level (I² = 87%) was observed․ The findings support DI as an effective pedagogical approach in multilingual English classrooms, consistently demonstrating its positive impact on grammar, reading comprehension, fluency, and overall language achievement compared to traditional approaches․ However, substantial variability in effect sizes highlighted the influence of educational contexts, student characteristics, and DI implementation strategies․ Methodological concerns, particularly regarding randomization and allocation concealment, also limited internal validity and generalizability․ Despite these limitations, the findings reinforce DI’s potential to promote equitable learning and enhance student engagement, advocating for its broader application in multilingual settings․ Future research should adopt more rigorous experimental designs, longitudinal approaches, and comprehensive evaluations of implementation fidelity, while exploring contextual factors that shape DI effectiveness, to refine both theoretical frameworks and practical guidelines․